Trend Learning Media of Elementary Education Indonesian Teacher in Practice Field Experience - Faidah Yusuf (Peneliti.net, 2023)
The teaching methods used in elementary school the practical experience of Indonesian teachers in the classroom still must be enhanced. The purpose of this study is to analyze, within the context of actual field experiences, the growing trend of educators making use of various forms of educational media in the classroom. The quantitative method was used for this analysis. Thirteen people were employed as the sample by applying each of the four-learning media at a variety of class levels. The total number of learning media that was studied was around 52. Within the scope of this study, it was determined that there are four distinct categories, namely school location, research subject, learning model, and learning media. the findings, all of which can show results in each finding related to the location of teachers applying in elementary schools located in villages, cities, and isolated areas, then various research subjects, there are low class and high class, the most frequently used PBL learning model, and power point media, which is a solution for teachers to convey material in class. Therefore, this study showed that the majority of teachers applying in elementary schools’ location, research subject, learning model, and learning media could be implemented